VOLATILE ORGANIC COMPOUND (VOC) EMISSION IN A UNIVERSITY PRINTING PRESS FACILITY IN EASTERN NORTH CAROLINA - Reese, Kellyn (East Carolina University, 2018)
Many printing facilities use large scale printing presses to meet their order demand. Printing presses are known to release volatile organic compounds (VOCs) that may be potentially hazardous to the health of print workers and staff. Long term exposure to specific VOCs may lead to serious health outcomes affecting the blood, kidneys, liver, brain or central nervous system. The purpose of this study is to investigate the airborne total VOC (TVOC) and toluene concentrations throughout the workday in an eastern North Carolinian university printing facility. Specifically, the study aims to determine the differences in TVOC concentrations by time of day, by day of the week, and by printing location, and to determine the 8-hour time-weighted-average (TWA) toluene exposures in the offset printing area. Photoionization detectors (PID) were utilized to measure the real-time TVOC concentrations for ~8 hours during each sampling day within a 6-week sampling period in 2 sampling locations (offset printing [OP] and digital printing [DR] areas) within the facility. Air samples were also collected using activated charcoal tubes at a flow rate of 0.20 liters per minute (LPM), and sent to an accredited laboratory for toluene analysis to determine the 8-hour TWA exposure. The mean daily TVOC concentration per sampling day was calculated by using all 1-second PID readings obtained during the work shift. One-way analysis of variance (ANOVA) test was used for the comparison of mean TVOC concentrations by printing location. P<0.05 was considered statistically significant. Results showed that the mean daily TVOC concentrations (n=38) have an overall average of 6.68 ± 3.25 ppm for the entire study. The mean daily TVOC concentrations in the OP area (8.99 ± 2.93 ppm) is significantly higher (p < 0.01) than that in the DR area (4.38 ± 1.38 ppm), which may be attributed to the type of printing equipment used. Both the lowest and highest mean daily TVOC concentrations (2.46 ± 1.35 ppm and 15.77 ± 5.69 ppm, respectively) were measured in the OP area. The maximum 1-second TVOC level was measured at 42.59 ppm in the OP area. The differences in TVOC concentrations between days may be attributed to the differences in workload (light vs heavy), while the differences within the day may be due to the specific tasks performed (e.g., ink loading, cleaning with solvents). The overall mean toluene concentration (n = 9) was 0.14 ± 0.10 ppm, with a range of 0.04 – 0.31 ppm which are below the OSHA PEL-TWA (200 ppm), NIOSH REL-TWA (100 ppm) and ACGIH TLV-TWA (20 ppm). Findings of this study will help in further understanding the nature of offset printing and digital printing processes and in planning to improve worker protection in printing and other similar industries based on important factors, such as location, equipment, and workload.
Keywords: VOCs, printing, toluene